Consensus statement—graft treatment in cardiovascular bypass graft surgery - Emmert, Maximilian Y.; Bonatti, Johannes; Caliskan, Etem; Gaudino, Mario; Grabenwöger, Martin; Grapow, Martin T.; Heinisch, Paul Phillip; Kieser-Prieur, Teresa; Kim, Ki-Bong; Kiss, Attila; Mouriquhe, Fatima; Mach, Markus; et al. (Frontiers in Cardiovascular Medicine, 2024)
Coronary artery bypass grafting (CABG) is and continues to be the preferred revascularization strategy in patients with multivessel disease. Graft selection has been shown to influence the outcomes following CABG. During the last almost 60 years saphenous vein grafts (SVG) together with the internal mammary artery have become the standard of care for patients undergoing CABG surgery. While there is little doubt about the benefits, the patency rates are constantly under debate. Despite its acknowledged limitations in terms of long-term patency due to intimal hyperplasia, the saphenous vein is still the most often used graft. Although reendothelialization occurs early postoperatively, the process of intimal hyperplasia remains irreversible. This is due in part to the persistence of high shear forces, the chronic localized inflammatory response, and the partial dysfunctionality of the regenerated endothelium. “No-Touch” harvesting techniques, specific storage solutions, pressure controlled graft flushing and external stenting are important and established methods aiming to overcome the process of intimal hyperplasia at different time levels. Still despite the known evidence these methods are not standard everywhere. The use of arterial grafts is another strategy to address the inferior SVG patency rates and to perform CABG with total arterial revascularization. Composite grafting, pharmacological agents as well as latest minimal invasive techniques aim in the same direction. To give guide and set standards all graft related topics for CABG are presented in this expert opinion document on graft treatment.